2001
DOI: 10.1116/1.1382879
|View full text |Cite
|
Sign up to set email alerts
|

HfO2–SiO2 interface in PVD coatings

Abstract: Structure of the interfacial region between polycarbonate and plasma-deposited SiN 1.3 and SiO 2 optical coatings studied by ellipsometry Hafnium oxide presents a strong interest either for optical coatings or for microelectronic applications. An important parameter to control is its chemical interaction with silicon oxide, since those two materials are usually in direct contact in both applications: For optical coatings, silica is the low refractive index used to make interference filters ͓see M. R. Kozlowski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 11 publications
1
22
1
Order By: Relevance
“…This, in turn, may lead to incorrect assignments and conclusions. For example, the binding energy of the Hf 4 f 7/2 levels of a thick film HfO 2 can be estimated as 17.3 and 17.4 eV from the recently published data of Wilk et al and Cosnier et al,respectively,[6][7][8] again differing by about 1 eV from the previously reported values. Additional confusion may arise from incorrect assignment of the surface and the bulk states.…”
Section: Introductioncontrasting
confidence: 39%
See 1 more Smart Citation
“…This, in turn, may lead to incorrect assignments and conclusions. For example, the binding energy of the Hf 4 f 7/2 levels of a thick film HfO 2 can be estimated as 17.3 and 17.4 eV from the recently published data of Wilk et al and Cosnier et al,respectively,[6][7][8] again differing by about 1 eV from the previously reported values. Additional confusion may arise from incorrect assignment of the surface and the bulk states.…”
Section: Introductioncontrasting
confidence: 39%
“…[5][6][7][8][9] As a result, extensive use of XPS and other surface techniques have recently been reported on hafnium oxide and related systems. [6][7][8][10][11][12] Although HfO 2 has a moderately high dielectric constant and band gap ͑both useful for ultrathin dielectric applications in micro-or nano-electronics͒, charging during photon or electron irradiation can make it difficult to determine the binding energies and/or the chemical states accurately. This, in turn, may lead to incorrect assignments and conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…The negative absorption feature at ∼1250 cm −1 is assigned to the loss of absorbance from Si-O stretching vibrations in the SiO 2 substrate. 44 The positive absorption feature at ∼1000 cm −1 is attributed to the gain of absorbance from Si-O-Hf stretching vibrations in hafnium silicate. 41,44,45 The hafnium silicate forms almost entirely during the first two HfO 2 ALD cycles on the SiO 2 nanoparticles at 200…”
Section: Ftir Spectroscopy Measurements-in Situ Ftir Spectra Of Hfo mentioning
confidence: 99%
“…The atomic composition, after a Shirley-type background subtraction was evaluated by using sensitivity factors supplied by Perkin-Elmer. [23,25] Depth profiles were carried out by Ar + sputtering at 3 keV with an argon partial pressure of 5 ϫ 10 -6 Pa. A specimen area of 2 ϫ 2 mm 2 was sputtered. Samples were introduced directly by a fast entry lock system into the XPS analytical chamber.…”
Section: Methodsmentioning
confidence: 99%